Kearifan Ekologi Masyarakat Adat Karampuang dalam Menjaga Kelestarian Hutan - Saudi, Muammar; Saudi, Muallim (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
The paradigm of world religions strongly influences insights about religion in Indonesia. The world's religious paradigm has placed indigenous people in discrimination, and they have difficulty carrying out the religious practices they have been doing for generations. This paper is a critical study of previous studies on the Karampuang Indigenous people, who still view traditions, community and nature relations, and local wisdom through the paradigms of world religions. This article will be examined through a traditional religious approach. This article aims to explain the relationship between the Karampuang Indigenous people and nature, the ecological wisdom of the Karampuang Indigenous people in preserving nature, and the traditions of the Indigenous people in maintaining this ecological wisdom. This study used a qualitative descriptive method with data collection techniques through interviews with key informants supported by the literature. First, it was found that the Karampuang Indigenous people see nature as a subject or person. This relationship is interpreted as Mapakalebbi Ale Hanua (respect for nature. Relationships are built because of the awareness that humans are integral to the forest itself. Second, ecological wisdom in the Karampuang community is passed down from generation to generation through Paseng (messages) of indigenous through Lontara and oral speech such as Makkamase Ale (loving the forest), Mappakatuo Ale (humanizing the forest) and Tuo Kamase-mase (living equal and in harmony with nature). Rituals of the Mappogau Sihanua are a reminder of the importance of preserving nature.